2007
DOI: 10.1159/000104237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Alcoholic Compounds of Alcoholic Drinks on the Pancreas

Abstract: unknown, caution is required in attempting to define alcoholic etiology of pancreatitis without considering the effect of non-alcoholic compounds of alcoholic beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(22 reference statements)
0
13
0
1
Order By: Relevance
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…2,21,22 Moreover, quercetin has been shown to inhibit amylase release induced by agonists such as cholecystokinin, carbachol, phorbol ester tetra decanoylphorbol-13--acetate. [23][24][25] A recent study has shown that one hour after the last dose of cerulein administration, quercetin treatment attenuates the development of AP in mice. The aim of the present study was to evaluate the protective and therapeutic effects of quercetin on pancreatic injury in cerulein-induced acute pancreatitis in rats.…”
Section: Methodsmentioning
confidence: 99%
“…Wiadomo, że alkohol etylowy wprowadzony dożylnie hamuje międzytrawienną aktywność zewnątrzwydziel-niczą tego narządu. Jednak w warunkach normalnych, kiedy napoje alkoholowe są przyjmowane doustnie, najczęściej zresztą razem z pokarmami, ich wpływ na egzokrynną czynność trzustki zależy nie tylko od stę-żenia etanolu, lecz także od oddziaływania składników niealkoholowych [82,83]. W badaniach Hajnala i wsp.…”
Section: Wpływ Napojów Alkoholowych Na Trzustkęunclassified